Redescription of Jatropha andrieuxii Muell. Arg. (Euphorbiaceae), an endemic species of southern Mexico - Jimenez Ramirez, Jaime; Martinez Gordillo, Martha (Instituto de Ecología, A.C., 1994)
The description of Jatropha andrieuxii Muell. Arg. is ampliated; habitat data as well as an illustration are included. Its transfer from section Curcas (Adans.) Griseb. to section Platyphyllae Dehgan et Webster is proposed on account of its gamopetalous corolla and biseriate stamens.